2015
DOI: 10.4414/smw.2015.14172
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of maternal and fetal pregnancy factors on the in-vitro induction of human regulatory T cells: a preliminary study

Abstract: Compared with circulating maternal factors, placental- and fetal-derived factors appear to exert a more powerful effect on numerical changes of Treg, thereby supporting fetomaternal tolerance during human pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…This unique subpopulation of T cells has shown to be involved in preventing autoimmunity, and tolerating allogeneic organ grafts in rodent models. The suppressive activity of Tregs is mediated either in a cell‐cell contact‐mediated fashion via cytotoxic T lymphocyte‐associated protein 4 (CTLA‐4) or by the secretion of cytokines such as transforming growth factor beta (TGF‐β) or interleukin (IL)‐10 . In 1995, Sakaguchi et al characterized a subpopulation of T cells with suppressive capacity .…”
Section: Regulatory T Cells: Phenotype and Functionmentioning
confidence: 99%
“…This unique subpopulation of T cells has shown to be involved in preventing autoimmunity, and tolerating allogeneic organ grafts in rodent models. The suppressive activity of Tregs is mediated either in a cell‐cell contact‐mediated fashion via cytotoxic T lymphocyte‐associated protein 4 (CTLA‐4) or by the secretion of cytokines such as transforming growth factor beta (TGF‐β) or interleukin (IL)‐10 . In 1995, Sakaguchi et al characterized a subpopulation of T cells with suppressive capacity .…”
Section: Regulatory T Cells: Phenotype and Functionmentioning
confidence: 99%
“…With respect to Tregs, a research report has demonstrated that not only the numbers of Tregs are decreased but the function of Tregs are also impaired in preeclampsia [66]. Other researchers have shown, albeit in small numbers, lower peripheral and decidual Treg sub-types in pregnancies complicated with preeclampsia [67][68][69][70][71][72]. In addition, derangement in the differentiation of recent thymic emigrant (RTE) Tregs have been observed in women with PE [73,74].…”
Section: Tregs and Preeclampsiamentioning
confidence: 99%